Positively Biased Processing of Mother’s Emotions Predicts Children’s Social and Emotional Functioning - Donohue, Meghan Rose (Early Child Res Q, 2016)
Risk for internalizing problems and social skills deficits likely emerges in early childhood when emotion processing and social competencies are developing. Positively biased processing of social information is typical during early childhood and may be protective against poorer psychosocial outcomes. We tested the hypothesis that young children with relatively less positively biased attention to, interpretations of, and attributions for their mother’s emotions would exhibit poorer prosocial skills and more internalizing problems. A sample of 4- to 6-year-old children (N=82) observed their mothers express happiness, sadness and anger during a simulated emotional phone conversation. Children’s attention to their mother when she expressed each emotion was rated from video. Immediately following the phone conversation, children were asked questions about the conversation to assess their interpretations of the intensity of mother’s emotions and misattributions of personal responsibility for her emotions. Children’s prosocial skills and internalizing problems were assessed using mother-report rating scales. Interpretations of mother’s positive emotions as relatively less intense than her negative emotions, misattributions of personal responsibility for her negative emotions, and lack of misattributions of personal responsibility for her positive emotions were associated with poorer prosocial skills. Children who attended relatively less to mother’s positive than her negative emotions had higher levels of internalizing problems. These findings suggest that children’s attention to, interpretations of, and attributions for their mother’s emotions may be important targets of early interventions for preventing prosocial skills deficits and internalizing problems.